Multistate study on suicide risk reduction and improving mental well-being among school and college students in India – an implementation research study protocol - Mehrotra, Seema; Duggal, Chetna; Rustagi, Neeti; Ransing, Ramdas Sarjerao; Indu, Pillaveetil Sathyadas; Chakraborty, Satabdi; Mene, Tarun; Sharma, Pragya; Prasad, Deepshikha; Prinja, Shankar; Verma, Pulkit; Dhamija, Rajinder K.; et al. (Frontiers in Public Health, 2025)
Suicide remains a crucial public health concern in India, especially among students and young adults. The growing academic pressure, social stigma, and lack of accessible mental health services contribute to the growing crisis and suicide rates in India. The study aims to develop an implementation model for educational institutions for reducing risk of suicide behavior (perceived stress and depressive symptoms) and enhance help-seeking behavior. This multi-sectoral implementation model is grounded in the WHO’s recommendation for youth suicide prevention and UMMEED guidelines. The study will adopt a concurrent mixed methods design, incorporating both quantitative and qualitative aspects that would be captured simultaneously. A formative research phase will be initially conducted before taking on the main study and it will be guided by the Updated Consolidated Framework for Implementation Research (CFIR). Additionally, the evaluation of the implementation process will be structured using the RE-AIM framework. The study participants will be school and pre-university students, and college students The expected outcome will be achieving reduction of suicide risk behaviors among school and college students in selected districts. The key barriers and facilitators identified through this implementation research will inform recommendations for the potential nation-wide scale up of strategies aimed suicide prevention strategies at educational institutes.Clinical trial registrationClinicalTrials.gov, CTRI/2024/08/072027.